Preliminary sensory characterisation of the diverse astringency of single cultivar Italian red wines and correlation of sub‐qualities with chemical composition. (5th May 2020) - Piombino, P.; Pittari, E.; Gambuti, A.; Curioni, A.; Giacosa, S.; Mattivi, F.; Parpinello, G.P.; Rolle, L.; Ugliano, M.; Moio, L.
Abstract: Background and Aims: Italy is the richest grape‐producing country in terms of cultivars. Our aims were to describe the diversity of astringency of Italian red wines from 11 cultivars, Teroldego, Corvina, Raboso, Nebbiolo, Sangiovese, Sagrantino, Montepulciano, Cannonau, Aglianico, Primitivo and Nerello, and to test correlations between in‐mouth sensory variables and chemical composition. Methods and Results: A sample sub‐set was selected by sorting and then assessed on astringency sub‐qualities (drying, harsh, unripe, dynamic, complex, surface smoothness, particulate) and tastes (sweet, acid, bitter). Inter‐cultivar differences were detected for six of the seven sub‐qualities: three diverse intensities for drying, two for harsh, unripe, dynamic, complex and velvet and none for particulate. Discriminant analysis showed that these sub‐qualities allowed a good discrimination of the wines according to the cultivar. Well reclassified samples (88%) were considered to develop a single‐cultivar 'astringency spectra', profiles describing the balance among sub‐qualities. Correlations highlighted that neither total phenols nor proanthocyanidins can predict the perception of all astringency nuances. Conclusions: For some single cultivar wines, it was possible to identify a pattern of astringency features likely to be linked to the cultivar. Significance of the Study: This work adds insights to the understanding of astringency sub‐qualities while enhancing the knowledge of Italian wines. Results may support the awareness of winemakers of wines from native cultivars, and assist in building models of astringency.